Formulation of a Design Concept for Arts and Culture Facilities in Banyuwangi City Using a Neo-Vernacular Architectural Approach - Dani Firmansyah; Muhammad Faisal; Tigor Wilfritz Soaduon Panjaitan (Kirana Publisher (KNPub), 2026)
The design of arts and cultural facilities in the city of Banyuwangi requires an understanding of local cultural characteristics so that the resulting buildings not only serve as venues for artistic activities but are also capable of representing the region’s identity. As an area rich in the traditions, arts and culture of the Osing people, Banyuwangi has great potential to provide facilities that support the sustainable preservation, development and promotion of culture. This research aims to formulate a design concept for Arts and Culture Facilities using a Neo-Vernacular Architecture approach that integrates local cultural values into modern architecture. The methods employed include literature review, field observation, spatial needs analysis, and an assessment of Banyuwangi’s environmental and socio-cultural conditions. The research results produced a design concept that emphasises local cultural identity, user comfort, spatial flexibility, and environmental sustainability through the application of distinctive Banyuwangi architectural elements in the massing, building form, and site layout. This concept is expected to serve as the foundation for realising arts and culture facilities that are functional, representative, and capable of becoming a centre for the preservation and development of Banyuwangi’s culture.